2004
DOI: 10.1093/hmg/ddh176
|View full text |Cite
|
Sign up to set email alerts
|

Full spectrum of malformations in velo-cardio-facial syndrome/DiGeorge syndrome mouse models by altering Tbx1 dosage

Abstract: Velo-cardio-facial syndrome/DiGeorge syndrome (VCFS/DGS) is associated with de novo hemizygous 22q11.2 deletions and is characterized by malformations attributed to abnormal development of the pharyngeal arches and pouches. The main physical findings include aortic arch and outflow tract heart defects, thymus gland hypoplasia or aplasia and craniofacial anomalies. The disorder varies greatly in expressivity; while some patients are mildly affected with learning disabilities and subtle craniofacial malformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
179
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(191 citation statements)
references
References 49 publications
9
179
0
Order By: Relevance
“…This hypothesis is compatible with what is already documented in some microdeletion syndromes, for example in 22q11.2 (Xu et al, 2013) and with what has been observed in cases of 17q12 duplication, where over-expression of miR-2909 could cause the decrease of the levels of FOXP2 expression: in fact several studies described deletions of this gene as responsible for language and cognitive disorders. It is widely accepted that, deletion and duplication of dose sensitive genes, as in 22q11 deletions/duplication, may cause a similar phenotype: mice over-and underexpressing TBX1 result in phenotypes similar to that of velocardiofacial syndrome (VCFS) (Liao et al, 2004). Thus we suggest that FOXP2 could be characterized by a similar mechanism, and therefore speech delay and cognitive impairment observed in our patient may be caused by miR-2909 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is compatible with what is already documented in some microdeletion syndromes, for example in 22q11.2 (Xu et al, 2013) and with what has been observed in cases of 17q12 duplication, where over-expression of miR-2909 could cause the decrease of the levels of FOXP2 expression: in fact several studies described deletions of this gene as responsible for language and cognitive disorders. It is widely accepted that, deletion and duplication of dose sensitive genes, as in 22q11 deletions/duplication, may cause a similar phenotype: mice over-and underexpressing TBX1 result in phenotypes similar to that of velocardiofacial syndrome (VCFS) (Liao et al, 2004). Thus we suggest that FOXP2 could be characterized by a similar mechanism, and therefore speech delay and cognitive impairment observed in our patient may be caused by miR-2909 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…46 -49 Interestingly, it has been observed in mouse models that both over-and under-expression of TBX1 recapitulates the DGS/ VCFS phenotype. 50,51 Recently, gain of function mutations in TBX1 have been reported patients with overlapping phenotypes with DGS/VCFS. 49,52 The above studies suggest that TBX1 dosage outside of normal range may affect the same developmental pathways in humans and contribute to the DGS/ VCFS and the 22q11.2 duplication syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, deletion of any of these genes results in aplasia or severe dysgenesis of the gland (Kimura, 1996;De Felice et al, 1998;Mansouri et al, 1998;Martinez Barbera et al, 2000). Transcription factors regulating pharyngeal arch development, e.g., Hox (Manley and Capecchi, 1998), Eya1 (Xu et al, 2002), and Tbx1 (Liao et al, 2004) contribute also to the formation and maturation of the ultimobranchial bodies. Interestingly, Nkx2.1 is the only transcription factor so far known to be expressed in both the thyroid diverticulum and the ultimobranchial bodies (Mansouri et al, 1998), suggesting that mechanisms governing their development might in part follow similar regulatory pathways.…”
Section: Introductionmentioning
confidence: 99%